The Role Of Perceived Value And Perceived Trust To Optimize Repeat Purchase Intention Based On Mean-End Chain Theory In Generations Y And Z - Ulin Nafisyah; Endy Gunanto Marsasi (Universitas Trunodjoyo Madura, 2023)
One sector that continues to experience development is the telecommunications sector. Telecommunications can make it easier to obtain information and carry out various activities. The communication sector has a vital role in the continuity and smoothness of communication. The objective of this research is to establish the correlation between the perceived price, perceived trust, perceived value, satisfaction, and repeat purchase intention of an Internet telecommunication service among individuals belonging to Generation Y and Z. The researchers introduce perceived trust as a new and innovative aspect of their study. Mean-End Chain Theory is used in research as the leading theory. The method in this study uses a quantitative approach using purposive sampling techniques, which resulted in 155 samples. The analytical approach utilised in the present investigation was. Structural Equation Modelling (SEM), using the AMOS Graphics 24 programmed. The study's findings suggest that the perceived price has a notable adverse impact on satisfaction. The perceived price and perceived trust favourably and dramatically effect the perceived value. This research is helpful in that mobile provider managers should improve perceived trust and perceived price of services by contributing to an event and being active in online marketing.